2018
DOI: 10.1016/j.ebiom.2017.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Global Transcriptome Analysis of RNA Abundance Regulation by ADAR in Lung Adenocarcinoma

Abstract: Despite tremendous advances in targeted therapies against lung adenocarcinoma, the majority of patients do not benefit from personalized treatments. A deeper understanding of potential therapeutic targets is crucial to increase the survival of patients. One promising target, ADAR, is amplified in 13% of lung adenocarcinomas and in-vitro studies have demonstrated the potential of its therapeutic inhibition to inhibit tumor growth. ADAR edits millions of adenosines to inosines within the transcriptome, and while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 47 publications
4
28
0
Order By: Relevance
“…A broadly negative relationship between editing and transcript abundance also fits with a mechanism by which mRNA expression is controlled through preferential retention of edited transcripts in the nucleus (Zhang and Carmichael 2001;Prasanth et al 2005), or a mechanism whereby mature mRNA abundance is reduced due to altered splicing mediated by RNA editing (Fei et al 2016). We note, however, that these results are different to those reported recently by Sharpnack et al (2018), who observed a positive association between RNA editing and gene expression, acknowledging that this was in the context of lung adenocarcinoma.…”
Section: Relationships Between Editing Doublestrandedness and Transsupporting
confidence: 83%
See 1 more Smart Citation
“…A broadly negative relationship between editing and transcript abundance also fits with a mechanism by which mRNA expression is controlled through preferential retention of edited transcripts in the nucleus (Zhang and Carmichael 2001;Prasanth et al 2005), or a mechanism whereby mature mRNA abundance is reduced due to altered splicing mediated by RNA editing (Fei et al 2016). We note, however, that these results are different to those reported recently by Sharpnack et al (2018), who observed a positive association between RNA editing and gene expression, acknowledging that this was in the context of lung adenocarcinoma.…”
Section: Relationships Between Editing Doublestrandedness and Transsupporting
confidence: 83%
“…Given the observation of widespread editing across diverse mammary transcripts, we wondered what physiological effects might be attributable to these modifications. Since editing has previously been proposed as a mechanism to modulate gene expression through microRNA-based mechanisms (Liang and Landweber 2007;Wang et al 2013;Brümmer et al 2017), through nuclear retention (Zhang and Carmichael 2001;Prasanth et al 2005), or by preventing activation of the MDA5-MAVS interferon response (Sharpnack et al 2018), we looked at the relation-ship between Φ-values and transcript abundance by calculating Pearson correlation coefficients for each implicated gene. For this analysis, we were particularly interested in the impacts on mRNA, so to best represent spliced transcripts, transcript abundance was quantified using reads that either mapped wholly within exons, or mapped across exon-exon boundaries (see Materials and Methods).…”
Section: Relationship Between Rna Editing and Transcript Abundancementioning
confidence: 99%
“…These sites include previously reported hotspots (frequently edited) with pathogenic role (e.g. EIF2AK2, MAVS, GATC, CTSS, METTL7A) 34,42,[44][45][46] as well as novel sites reported here for the first time (e.g.…”
Section: Discussionsupporting
confidence: 64%
“…Previous studies have demonstrated that ADAR1 inhibits miRNA processing globally through forming ADAR1/Dicer complex via the RNA interference machinery [158]. Although most ADAR editing occurs in non-coding regions in lung cancer, few studies have shown the crosstalk between ADAR and non-coding RNAs [159]. Anadon et al have demonstrated that ADAR1 gene amplification in NSCLC promotes tumor growth via enhanced A-to-I editing of RNA transcripts including miR-381 [160].…”
Section: Role Of Non-coding Rnas In Rna Editingmentioning
confidence: 99%